ILC3: a case of conflicted identity - Koprivica, Ivan; Stanisavljević, Suzana; Mićanović, Dragica; Jevtić, Bojan; Stojanović, Ivana; Miljković, Đorđe (Frontiers in Immunology, 2023)
Innate lymphoid cells type 3 (ILC3) are the first line sentinels at the mucous tissues, where they contribute to the homeostatic immune response in a major way. Also, they have been increasingly appreciated as important modulators of chronic inflammatory and autoimmune responses, both locally and systemically. Proper identification of ILC3 is of utmost importance for meaningful studies on their role in immunity. Flow cytometry is the method of choice for detection and characterization of ILC3. However, analysis of ILC3-related papers shows inconsistency in ILC3 phenotypic definition, as different inclusion and exclusion markers are used for their identification. Here, we present these discrepancies in the phenotypic characterization of human and mouse ILC3. We discuss pros and cons of using various markers for ILC3 identification. Further, we consider possibilities for efficient isolation and propagation of ILC3 from different organs and tissues for in vitro and in vivo studies. This paper calls upon uniformity in ILC3 definition, isolation and propagation for the increased possibility of confluent interpretation of ILC3 role in immunity.